Proceedings of the 6th Workshop on Argument Mining 2019
DOI: 10.18653/v1/w19-4512
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Discourse Parsing Features for Predicting Argumentation Structure

Abstract: Research on argumentation mining from text has frequently discussed relationships to discourse parsing, but few empirical results are available so far. One corpus that has been annotated in parallel for argumentation structure and for discourse structure (RST, SDRT) are the 'argumentative microtexts' (Peldszus and Stede, 2016a). While results on perusing the gold RST annotations for predicting argumentation have been published (Peldszus and Stede, 2016b), the step to automatic discourse parsing has not yet bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Discourse Relations Rhetorical Structure Theory was originally developed to offer an explanation of the coherence of texts. Musi et al (2018) and, more recently Hewett et al (2019), showed that discourse relations from RST often correlate with argumentative relations. We thus derive features from RST trees and train a classifier using these features to predict an argumentative relation.…”
Section: Methodsmentioning
confidence: 99%
“…Discourse Relations Rhetorical Structure Theory was originally developed to offer an explanation of the coherence of texts. Musi et al (2018) and, more recently Hewett et al (2019), showed that discourse relations from RST often correlate with argumentative relations. We thus derive features from RST trees and train a classifier using these features to predict an argumentative relation.…”
Section: Methodsmentioning
confidence: 99%
“…Other loosely related corpora (i.e., those which have not been annotated with argumentation structures but with other linguistic phenomena) can be used in auxiliary tasks. Examples include discourse relations in the Penn Discourse TreeBank (Prasad et al 2008;Hewett et al 2019) (such as subordinating and coordinating conjunctions, adverbials, and several kinds of implicit relations) and textual entailment/natural language inference Villata 2012, 2013;Choi and Lee 2018;Conneau et al 2018).…”
Section: Practical Compatibilitymentioning
confidence: 99%
“…The best performance is achieved when considering a subgraph of depth 3. RST parsing is first used to analyze arguments in Microtexts by Hewett et al (2019). The texts were analyzed with multiple earlier parsers, and the one proposed by Feng and Hirst (2014) was chosen based on the manual evaluation of the results.…”
Section: Background and Related Workmentioning
confidence: 99%